Perceived facial adiposity conveys information about women's health. (6th June 2012) - Tinlin, Rowan M.; Watkins, Christopher D.; Welling, Lisa L. M.; DeBruine, Lisa M.; Al‐Dujaili, Emad A. S.; Jones, Benedict C.
<x xml:space="preserve">Abstract</x> Although several prominent theories of human facial attractiveness propose that some facial characteristics convey information about people's health, empirical evidence for this claim is somewhat mixed. While most previous research into this issue has focused on facial characteristics such as symmetry, averageness, and sexual dimorphism, a recent study reported that ratings of facial adiposity (i.e., perceptions of fatness in the face) were positively correlated with indices of poor physical condition in a sample of young adults (i.e., reported past health problems and measures of cardiovascular fitness). These findings are noteworthy, since they suggest that perceived adiposity is a potentially important facial cue of health that has been overlooked by much of the previous work in this area. Here, we show that ratings of young adult women's facial adiposity are (1) better predicted by their body weight than by their body shape (Studies 1 and 2), (2) correlated with a composite measure of their physical and psychological condition (Study 2), and (3) negatively correlated with their trait (i.e., average) salivary progesterone levels (Study 3). Together, these findings present further evidence that perceived facial adiposity, or a correlate thereof, conveys potentially important information about women's actual health.